PHYSICAL AND PSYCHO-EMOTIONAL DISORDERS IN WOMEN WITH POSTPARTUM COMPLICATIONS - Kurbanova, J.F.; Sultanova, S.G.; Hajiyeva, F.R. (World of Medicine and Biology, 2022)
In terms of prevalence, one of the leading places in the structure of gynecological morbidity is occupied by postpartum complications. The aim was to study the quality of life in women with early postpartum complications. 150 puerperae were divided into two groups: the main group – women with puerperal complications (n=100) aged 29.9±0.64, the comparison group – puerperae with the physiological course of the postpartum period (n=50) at the age of 30.3±0.86 years (p=0.679). In puerperae data of the SF-36 quality of life questionnaire were obtained. Indicators revealed a significant decrease in the values on the scale “Physical functioning” in the main group, compared with the control group (63.3±0.80 and 82.3±0.86, respectively; p=0.0001) and statistically significant decrease in indicators on the “Mental Health” (MH) scale in the main group – 69.6±0.64, versus 77.8±1.03 in the control group (p=0.0001). Thus, women with early postpartum complications are characterized by an increase in restrictions in the performance of physical activity and a pronounced deterioration in the psycho-emotional state.
Keywords: postpartum period; complications; risk factors; quality of life; questionnaire SF-36